ID-based wireless authentication scheme with anonymity - ZHU Hui; LI Hui; SHU Wan-li; WANG Yu-min (Tongxin xuebao)
Considered the especial requirements of the authentication scheme among the roaming users and the visited networks,an ID-based wireless authentication scheme with anonymity was proposed by the bilinearity and non-degeneration of pairings.The security of authentication and anonymity was analyzed in detail.Especially,the anonymous security was analyzed by formal approach under the unauthenticated-links adversarial model.It is showed that the proposed scheme not only could achieve authentication securely but also has a secure anonymity,and could achieve the secure requirements of the wireless network.Moreover,the scheme is simple and efficient,and could be ap-plied to the authentication in the wireless network.